How the laser happened : adventures of a scientist - Townes, Charles H. (Oxford University Press, 2002)
Annotation In How the Laser Happened, Nobel laureate Charles Townes provides a highly personal look at some of the leading events in twentieth-century physics. Townes was inventor of the maser, of which the laser is one example; an originator of spectroscopy using microwaves; and a pioneer in the studyof gas clouds in galaxies and around stars. Throughout his career he has also been deeply engaged with issues outside of academic research. He worked on applied research projects for Bell Labs; served on the board of directors for General Motors; and devoted extensive effort to advising thegovernment on science, policy, and defense. This memoir traces his multifaceted career from its beginnings on the family farm in South Carolina. Spanning decades of ground-breaking research, the book provides a hands-on description of how working scientists and inventors get their ideas. It also gives a behind-the-scenes look at thescientific community, showing how scientists respond to new ideas and how they approach a variety of issues, from priority and patents to the social and political implications of their work. In addition, Townes touches on the sociology of science, uncovering some of the traditions and values thatare invisible to an outsider. A towering and energetic figure, Townes has explored or pioneered most of the roles available to the modern scientist. In addition to fundamental research, he was actively involved in the practical uses of the laser and in the court cases to defend the patent rights. He was a founding member of theJasons, an influential group of scientists that independently advises the government on defense policy, and he played an active part in scientific decisions and policies from the Truman through the Reagan administration. This lively memoir, packed with first-hand accounts and historical anecdotes, is an invaluable resource for anyone interested in the history of science and an inspiring example for students considering scientific careers.